Robust network topology for unbalanced active distribution networks with uncertain injections - Sanat Kumar Paul; Abheejeet Mohapatra; Dulal Chandra Das (IET Energy Systems Integration)
Abstract This research paper introduces a comprehensive formulation for robust dynamic network reconfiguration (NR) of unbalanced active electric distribution networks (DNs). Network reconfiguration is a potent strategy to minimise active power loss in DN as it involves altering network topology through sectionalising (normally closed) and tie‐line switches (normally open). However, NR is usually a mixed integer NP‐hard non‐linear optimisation problem due to the discrete nature of the switches. Hence, including variable injection uncertainties (from generation or load) for an unbalanced active DN with all its attributes further poses a significant challenge in solving NR. The proposed formulation addresses these challenges in a robust optimisation (RO) framework to get a robust topology and power and voltage set points for dispatchable Distributed Generators (DGs). Also, Chance‐Constrained robust formulations are proposed to regulate the conservatism of RO. Numerical analyses demonstrate the impact of conservative robust NR on DG set points compared to the non‐robust NR method. Tests on a modified unbalanced IEEE 34‐bus system and comparison with previous formulations verify the efficacy of the proposed approach, showcasing its effectiveness.